(untitled) (SCIENCE TIME JOURNAL, 2026)
The history of foreign language teaching (FLT) methodology is one of successive paradigm shifts, from the grammar-translation method through the audio-lingual and communicative approaches to the complex, culturally oriented frameworks of the present. This article argues that the most consequential contemporary shift is the reframing of FLT through the lens of intercultural communicative competence (ICC). The article contends that genuine ICC integration requires not merely the addition of cultural content to existing language courses but a structural reconceptualisation of the objectives, methods, materials, and assessment practices of FLT. A comparative framework and an instructional integration matrix are presented as practical analytical tools for curriculum developers and teacher educators.